Algorithms and data structures : 9th International Workshop, WADS 2005, Waterloo, Canada, August 15-17, 2005 : proceedings - Workshop on Algorithms and Data Structures; Dehne, Frank; López-Ortiz, Alejandro; Sack, Jörg-Rüdiger (Lecture Notes in Computer Science / Theoretical Computer Science, 2005)
A collection of papers that address searching and sorting, approximation, graph and network computations, computational geometry, randomization, communications, combinatorial optimization, scheduling, routing, navigation, coding, and pattern matching.